La lista impensabile (ENTHYMEMA, 2013)
This paper wants to analyse the theme of collecting and the figure of the collector by including them in a series of connected concepts in order to devise a multidisciplinary conceptual map. In particular, the analysis is focusing on these points: the relationship between man and object, and between object and series; the dynamics of desire related to the problem of choosing the object; the fetishism – in which object and desire meet. Broadly speaking, the emblematic personality of the collector, the complexity of the relationship between past and present, and the survival of the past in collecting, especially in antique trade.